Gutted: Beautiful Horror Stories by Clive Barker, Neil Gaiman, Ramsey Campbell, Kevin Lucia - Doug Murano; D. Alexander Ward (Crystal Lake Publishing, 2016)
From Bram Stoker Award-nominated publisher, Crystal Lake Publishing, and the editing duo who brought you the best-selling and critically acclaimed small-town Lovecraftian horror anthology Shadows Over Main Street, comes Gutted: Beautiful Horror Stories-a disturbing journey into the beauty that rests inside the very heart of darkness. Awe meets ache. Terror becomes transcendence. Regret gives way to rebirth. Fifteen short stories and one poem span nearly every twisted corner of the horror and dark fiction genres: A woman experiences an emotional reckoning inside a haunted house. A father sees his daughter rescued after a cold case is solved, only to learn the tragic limits of his love. A man awakens a vengeful spirit and learns the terrible price of settling scores. A boy comes of age into awareness of a secret universe of Lovecraftian scale. A young woman confronts the deathly price of existence inside a German concentration camp during the Holocaust. And much, much more... Gutted: Beautiful Horror Stories features the most celebrated voices in dark fiction, as well as a number of exciting, new talents, including: Clive Barker, Neil Gaiman, Ramsey Campbell, Paul Tremblay, John F.D. Taff, Lisa Mannetti, Damien Angelica Walters, Josh Malerman, Christopher Coake, Mercedes M. Yardley, Brian Kirk, Stephanie M. Wytovich, Amanda Gowin, Richard Thomas, Maria Alexander and Kevin Lucia. With a foreword from Cemetery Dance magazine founder Richard Chizmar.
Keywords: Horror; Short Stories; Fiction